Colorectal cancer mutations are associated with survival and recurrence after pulmonary metastasectomy. Issue 4 (9th July 2019) - Corsini, Erin M.; Mitchell, Kyle G.; Mehran, Reza J.; Rice, David C.; Sepesi, Boris; Walsh, Garrett L.; Swisher, Stephen G.; Roth, Jack A.; Hofstetter, Wayne L.; Vaporciyan, Ara A.; Morris, Van K.; Antonoff, Mara B.
Abstract: Background and Objectives: While knowledge has grown extensively regarding the impact of mutations on colorectal cancer prognosis, their role in outcomes after pulmonary metastasectomy (PM) remains minimally understood. We sought to determine the prognostic role of mutant disease on survival and recurrence after metastasectomy. Methods: Patients with available tumor sequencing profiles who underwent PM for colorectal cancer at a single institution from 2011 to 2017 were reviewed. Various demographic and clinicopathologic factors, as well as mutational status, were tested in the Cox regression analyses to identify predictors of survival and disease‐free survival (DFS). Results: A total of 130 patients met inclusion criteria, among whom 78 (60%) were male and the mean age was 57 years. The median survival time and 5‐year survival rate were 58.2 months and 47%, respectively. A single pulmonary nodule was present in 54%. Disease recurrence occurred for 87 (67%) patients, including 75 (58%) who had at least one lung recurrence after metastasectomy at a median time to recurrence of 19.4 months. Upon multivariable analysis, RAS and TP53 mutations were associated with shorter survival DFS, while APC is associated with prolonged survival. Conclusions: After metastasectomy for colorectal cancer, mutations in RAS, TP53, and APC play an important role in survival and recurrence.